Smart Cultural Heritage : Strategi Wujudkan Cultural Capital Desa Tulusbesar Melalui Program Mojangki (Monggo Sanjang Mriki Space) Inovasi Desa Budaya Tulusbesar - Elvina Eka Saputri; Siska Nurnaningati; Tri Ayu Mukaromatul (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The rapid development of technology and local wisdom that must be maintained is a challenge for the younger generation to coexist with technology. The flow of globalization is one of the challenges that will trigger the dynamics of national identity, this refers to the negative impact caused by globalization, especially on the cultural dimension (Julianty et al., 2022). Indonesia is a country that has a lot of cultural diversity and natural beauty. One of them is in Tulusbesar Village. Tulusbesar Village is a village in Tumpang District, Malang Regency that has potential in the field of culture. Tulusbesar Village has facilities to support the existence of arts in the Tulusbesar Village area. From the various artistic diversity in the village, there are problems in preserving culture, as well as a lack of understanding in digital, which also makes this village quite lagging behind in its cultural marketing. With the innovation of the Mojangki (Monggo Sanjang Mriki) Space program using the Smart Cultural Heritage (SmaCh) method, it aims to be able to realize the Cultural Capital of Tulusbesar Village so that it is always sustainable and survive to develop a cultural village.